Intersectional Stigma and Multi-Level Barriers to HIV Testing Among Foreign-Born Black Men From the Caribbean - Taylor, Tonya N.; DeHovitz, Jack; Hirshfield, Sabina (Frontiers in Public Health, 2020)
Testing is the entry point into the HIV care continuum that includes linkage to and retention in prevention services, and adherence to prevention strategies, including repeat HIV testing. Despite US policy approaches to expand HIV testing to diverse clinical care and community settings, disparities in HIV testing among Black populations persist. Foreign-born Black (FBB) persons from the Caribbean have higher annual rates of HIV diagnosis and a higher percentage of late-stage HIV diagnosis, compared with US-born Black persons; and most HIV infections among FBB persons are among men. In this article, we provide an overview of HIV testing barriers among high-risk FBB men, who are defined as men who have condomless sex with male and/or female partners of unknown HIV serostatus. Barriers to HIV testing for both FBB and US-born Black men, include HIV stigma (anticipated, perceived, internalized), low perceived HIV risk, medical or government mistrust, and perceived low access to testing resources. We examine beliefs about masculinity and gender roles that may perpetuate heteronormative stereotypes associated with low perceptions of HIV risk and barriers to HIV testing. We also discuss the impact of recent immigration policies on accessing HIV testing and treatment services and how intersectional stigmas and structural forms of oppression, such as racism, prejudice against select immigrant groups, and homophobia that may further amplify barriers to HIV testing among FBB men. Finally, we review comprehensive prevention approaches that may improve the uptake of HIV testing among FBB Black men.